Anxiety and Burnout Predict the Depression among Primary Caregivers of People with Schizophrenia in Sedayu II Public Health Centre Bantul - Sofyan Indrayana; Mulyanti Mulyanti (Alma Ata University Press, 2020)
Schizophrenia is defined as a severe mental illness characterized by disturbance of thinking, perception, and emotion. The role of caregiver is pivotal to help the patients’ daily needs such as bathing, eating, cooking, dressing, and taking medicines. Unfortunately, caregivers of schizophrenia patients tend to have depression greater than other population. It is because chronic diseases will affect not only physically but also psychological and financial as well for patients and family. To decide the appropriate intervention for schizophrenia caregivers to reduce depression among them, it is important to know the predictors of depression among the primary caregivers of people with schizophrenia in Sedayu II Public Health Centre Bantul. This study aimed to determine the predictors of depression among the primary caregivers of People with Schizophrenia in Sedayu II Public Health Centre Bantul. This was a non-experimental study with the cross-sectional approach. As much as 38 caregivers recruited by using the purposive sampling technique. Data was administrated using DASS questionnaire and Zarit Burden Scale. Two variables that having VIF < 10 and p-value of simple regression < 0.25 namely anxiety and burnout were included into multiple regression analysis. Most of caregivers were women (71.1%), elementary school educated (36.8%), marriage (78.9%), and unemployed (57.9%). All of participants were family of schizophrenia patients in Sedayu II Public Health Centre Bantul with the mean of age was 54.3 (±14.74). Multiple regression showed that this model resulted in the adjusted R2 0.717 (p<0.01) which means this model explained 71.7% of the variability of depression among caregivers of people with schizophrenia in Sedayu II Public Health Centre Bantul. Moreover, our study confirmed that the predictors of depression among caregivers of people with schizophrenia in Sedayu II Public Health Centre Bantul were anxiety (p=0.000) and burnout (p=0.002). Anxiety and burnout were the significant predictors of depression among caregivers of people with schizophrenia in Sedayu II Public Health Centre Bantul. Hence, some interventions reducing anxiety and burnout such as family psycho-education might help to prevent depression among them.